PENERAPAN PEMBELAJARAN BERDIFERENSIASI BERBANTUAN MEDIA TEKNOLOGI PADA MATERI TEKS NONFIKSI UNTUK SISWA KELAS VI SEKOLAH DASAR - Moh. Sholeh; Imam Rofiki (Universitas Islam Malang, 2024)
Education in the digital era demands innovation in learning methods, one of which is the use of technology. Teachers must understand that true education involves recognizing the nature and conditions of the child's age. Each student has different needs, learning styles, and learning speeds. Differentiated learning allows teachers to adjust teaching methods and materials to better suit the individual needs of students. Technology allows this personalization to be more effective and efficient through tools such as online learning platforms, adaptive software, and learning applications. The purpose of this article is to determine the application of differentiated learning assisted by technology media on non-fiction text materials. This descriptive study uses a qualitative approach. The participants in this study were one Indonesian language teacher and 26 elementary school students. Data were collected based on the results of observations, interviews, and documentation during classroom learning activities. The results of the study indicate that the content aspect applied in the learning is that the teaching materials used are animated videos, while in the process aspect students are asked to try to make an animated video from several non-fiction readings in the library. The product section is an animated video from the group that has been compiled based on a diagnostic assessment. Keywords: Differentiated Learning, Technology Media, Non-fiction Text.